Inflammatory Breast Diseases during Lactation: Health Effects on the Newborn-A Literature Review - Achim Wöckel; Michael Abou-Dakn; Anna Beggel; Petra Arck (Hindawi Limited, 2008)
Breastfeeding-associated inflammatory breast diseases appear especially during the first twelve weeks postpartum and are the most common reason for early cessation of breastfeeding. It also becomes increasingly evident that these inflammatory mammary diseases are triggered or perpetuated in a large part by psychosocial stress. Immunological processes taking place during this cascade in the mammary gland and consequences for the breastfeed newborn are mostly yet unknown. This review summarizes insights from studies on modulation of cytokine levels in breast milk during inflammatory processes like milk stasis and mastitis systematically. It also gives an overview on possible pathological effects, which these cytokine changes in the breast milk might have on the newborn.